2005
DOI: 10.1128/jvi.79.20.12773-12782.2005
|View full text |Cite
|
Sign up to set email alerts
|

TMC125 Displays a High Genetic Barrier to the Development of Resistance: Evidence from In Vitro Selection Experiments

Abstract: TMC125 is a potent new investigational nonnucleoside reverse transcriptase inhibitor (NNRTI) that is

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
181
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 229 publications
(196 citation statements)
references
References 35 publications
(32 reference statements)
10
181
0
Order By: Relevance
“…As a diarylpyrimidine, ETR has a high capacity for isomerization, which allows it to effectively bind to and inhibit common mutated forms of the viral enzyme (Andries et al, 2004;Vingerhoets et al, 2005;Gupta et al, 2011;Picchio et al, 2011). Therefore, ETR has a higher genetic barrier to viral resistance and as such is often prescribed for treatment-experienced patients who have developed mutations that confer resistance to first-generation NNRTIs (Lazzarin et al, 2007;Madruga et al, 2007;Nadler et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…As a diarylpyrimidine, ETR has a high capacity for isomerization, which allows it to effectively bind to and inhibit common mutated forms of the viral enzyme (Andries et al, 2004;Vingerhoets et al, 2005;Gupta et al, 2011;Picchio et al, 2011). Therefore, ETR has a higher genetic barrier to viral resistance and as such is often prescribed for treatment-experienced patients who have developed mutations that confer resistance to first-generation NNRTIs (Lazzarin et al, 2007;Madruga et al, 2007;Nadler et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The findings of this study showed high frequency of the primary NNRTI mutations including K103N, G190A, K103S, Y181Y/C, and Y188L that cause high-level resistance to nevirapine and variable resistance to efavirenz, ranging from 2-fold for Y181C, 6-fold for G190A, 20-fold for K103N and >50-fold for Y188L (29)(30)(31).…”
Section: ------------------------------------------------------------mentioning
confidence: 96%
“…[39][40][41] In addition, presence of the K103N (lysine to arginine) mutation that commonly confers resistance to first-generation NNRTIs is not associated with decreased virologic response to etravirine. 42 Seventeen RAMs have been associated with decreased susceptibility to etravirine.…”
Section: Resistancementioning
confidence: 99%